2017
DOI: 10.1016/j.jpeds.2016.09.069
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis is Associated with Adverse Neonatal Outcomes in Washington State, 1996-2013

Abstract: Objective To determine whether cystic fibrosis (CF) is associated with adverse neonatal outcomes in a recent birth cohort in the United States. Study design A retrospective matched cohort study of infants born in Washington State from 1996-2013 was identified through birth certificate data and linked to statewide hospital discharge data. Infants with CF were identified by hospitalization (through age 5 years) in which a CF-specific ICD-9 code was recorded. “Unexposed” infants lacked CF-related ICD-9 codes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
(44 reference statements)
1
6
0
1
Order By: Relevance
“…13 Factors contributing to the increased incidence of preterm birth among infants with CF are unknown, but it has been speculated that CFTR, expressed on the placenta, may affect gestational duration. 3,16 Despite the increase in preterm births that we observed, the rates of SGA (10.2%) and LBW (4.9%) in singleton infants our study were on par with the general population (SGA: 10%; LBW: 6.6%), 13,18 similar to what has been reported by the U.S. CF Foundation Data Registry. Both low birth weight and SGA infants were more likely to be of twin gestation, which is also consistent with general population characteristics.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…13 Factors contributing to the increased incidence of preterm birth among infants with CF are unknown, but it has been speculated that CFTR, expressed on the placenta, may affect gestational duration. 3,16 Despite the increase in preterm births that we observed, the rates of SGA (10.2%) and LBW (4.9%) in singleton infants our study were on par with the general population (SGA: 10%; LBW: 6.6%), 13,18 similar to what has been reported by the U.S. CF Foundation Data Registry. Both low birth weight and SGA infants were more likely to be of twin gestation, which is also consistent with general population characteristics.…”
Section: Discussionsupporting
confidence: 78%
“…It should be noted that while several previous single center or state studies have shown that neonates with CF have reduced birth weight compared to the general population, 2,3,16,17 we saw this as well in the entire study sample, but did not observe this when we looked only at full term infants, which may be a function of higher rates of prematurity in CF. In our study population 14.3% of singleton births were premature compared to ~10% in the general U.S. population, and for full term singleton infants in our study population, the mean birth weights for males and females were 3618 grams (n=598) and 3433 grams (n=556), respectively, with similar published 50th percentile birth weights for the general population (3580 and 3441 grams for males and females, respectively).…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…In another study, Darrah et al 1 compared the birth weight of 79 patients with CF born at term with pancreatic insufficiency and cared for at the Cystic Fibrosis Center at Rainbow Babies and Children’s Hospital in Cleveland, Ohio between 1975 and 2005 with the national average. In the study population, male babies with CF weighed an average 3239.80 g (SD=367.83 g, N=40) compared with a national average of 3530.20 g; female babies with CF weighed 3142.94 g (SD=422.75 g, N=39) compared with a national average of 3399.19 g. Recently, Ramos et al 13 conducted a study in Washington State comparing the birth weight of 170 babies with CF with that of 3400 babies with no CF matched by birth year and born between 1996 and 2013. They found mean birth weights of 3031 g (SD=759 g) and 3387 g (SD=581 g) for babies with and without CF, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…A közelmúltban a szintén egyesült államokbeli Washington államban végeztek egy tanulmányt, amelyben összehasonlították a cystás fibrosisban szenvedő betegek 170 újszülöttjének születési súlyát nem cystás fibrosis betegek 3400 újszülöttjének születési súlyával. Megállapították, hogy a betegek újszülöttjeinek születési súlya kisebb, mint a kontrolloké: 3031 ± 759 g vs. 3387 ± 581 g [42]. Újabban Dánia (1980 és 2010 közötti) és az egyesült királyságbeli Wales (1998 és 2015 közötti) nyilvántartási adatai alapján végeztek vizsgálatokat 852, cystás fibrosisban szenvedő nő gyermekei között.…”
Section: A Cystás Fibrosis Hatása a Magzatraunclassified